2018
DOI: 10.1021/acs.iecr.8b01533
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Reactive Extraction of Isonicotinic Acid Using Tri-n-octylamine in Biocompatible Diluents Mixture: Response Surface Methodology and Regeneration of Solvents

Abstract: The present study is aimed to recover the pharmaceutically and biochemically important compound, isonicotinic acid (iNA) from aqueous/fermentation broth in a biocompatible extraction system using an intensified approach, reactive extraction. Tri-n-octylamine (TOA) is used as extractant in nontoxic diluent mixtures of dodecane and n-decanol (modifier) in 1:1 v/v. However, modeling and optimization of reactive extraction using three process parameters, that is, initial iNA concentration in aqueous solution (0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Moreover, the highest z obtained with n -hexane was 0.018, indicating that the strength of the interaction between the solvent and acid–amine complex is extremely weak. The results and observations are consistent with previous reports in the literature. ,,,, In the literature, several studies focused on the modeling of reactive extraction process using linear regression, artificial neural network, and response surface methodology. In this study, a multilinear regression was applied to model the experimental data (Figure ). Table shows the values of R 2 , R 2 adj , RMSE, and coefficients obtained from the fits of the model for all solvents tested.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, the highest z obtained with n -hexane was 0.018, indicating that the strength of the interaction between the solvent and acid–amine complex is extremely weak. The results and observations are consistent with previous reports in the literature. ,,,, In the literature, several studies focused on the modeling of reactive extraction process using linear regression, artificial neural network, and response surface methodology. In this study, a multilinear regression was applied to model the experimental data (Figure ). Table shows the values of R 2 , R 2 adj , RMSE, and coefficients obtained from the fits of the model for all solvents tested.…”
Section: Resultssupporting
confidence: 88%
“…They suggested that solvents with a log P a value greater than 4 are nontoxic and biocompatible with the microbes. With log P a values greater than 4, oleyl alcohol, 88 dodecane, 200 and natural oils, 201 etc. are used by researchers to minimize the toxicity of organic phase.…”
Section: Solvent Selection For In-situ Acid Extraction From Fermentat...mentioning
confidence: 99%